If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8 * 4x + -8 = 0 Multiply 8 * 4 4x + 32x + -8 = 0 Reorder the terms: -8 + 4x + 32x = 0 Combine like terms: 4x + 32x = 36x -8 + 36x = 0 Solving -8 + 36x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 36x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 36x = 0 + 8 36x = 0 + 8 Combine like terms: 0 + 8 = 8 36x = 8 Divide each side by '36'. x = 0.2222222222 Simplifying x = 0.2222222222
| 10x=38.1 | | 4x-6*4x+6= | | -25=5x+10 | | x-7=2x-17 | | 10x+1=8x-3 | | -12=2x-2 | | -46-(-90)= | | 24=16+4x | | 2*-23= | | -46(-90)= | | 3=5y+2(y+1) | | 5-3*10= | | -24=7x-x | | 9=-6+5x | | 8m+8= | | 65=75-2x | | 16=24-x | | 42-x=28 | | (4x+3)(3x-2)(2x+1)= | | 12-3(x-2b)=5b-4x | | 4x+6y=1/8 | | h=3g+4 | | (2x-3)-7=4 | | 3x+4-2x-2= | | 3x/4=18 | | (x)+6=157 | | 3.142x^2-x-26(3.142)=0 | | (x-4)=72 | | (4*x)/((x-1)*((x^2)+1)) | | 5+10(x-4)=848 | | 4x+6w=1/8 | | x^3-x^2+x+1= |